A label-free electrochemical immunosensor for beta-amyloid detection. Issue 31 (27th July 2016) - Kaushik, Ajeet; Shah, Pratikkumar; Vabbina, Phani Kiran; Jayant, Rahul Dev; Tiwari, Sneham; Vashist, Arti; Yndart, Adriana; Nair, Madhavan
Abstract : A label-free detection of beta-amyloid (βA) proteins using an electrochemical immunosensor fabricated via immobilizing specific anti-beta-amyloid antibodies (An-βA-Abs) onto an interdigitated electrode of gold (IDE-Au) modified using a self-assembled monolayer (SAM) of dithiobis(succinimidyl propionate) [DTSP] is presented here. Abstract : A label-free detection of beta-amyloid (βA) protein using an electrochemical immunosensor fabricated via immobilizing specific anti-beta-amyloid antibodies (An-βA-Abs) onto an interdigitated electrode of gold (IDE-Au) modified using a self-assembled monolayer (SAM) of dithiobis(succinimidyl propionate) [DTSP] is presented here. The βA has been investigated as a potential biomarker for monitoring Alzheimer's disease (AD), permanent irreversible and progressive brain damage. Thus βA detection at the pM level is of high significance for AD diagnostics. The IDE-Au modification and covalent immobilization of An-βA-Abs onto electrodes were characterized by differential pulse voltammetry (DPV) and electrochemical impedance spectroscopy (EIS) as a function of electrical response variation in each step involved in sensor fabrication. The EIS studies confirmed that the developed βA immunosensor is selective and exhibits a detection limit of 10 pM, its detection range varies from 10 pM to 100 nM, and it has a high sensitivity of 11 kΩ M −1 with a regression coefficient of 0.99. Thus, the developed sensitive and selective immunosensor with the features of the IDE-Au can be integrated with a miniaturized potentiostat (M-P) to develop a sensing system to detect βA for point-of-care (POC) applications for the assessment and management of AD. The bio-informatics gathered from such a system could be useful to make timely therapeutic decisions.